2017
DOI: 10.1111/vox.12499
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion medicine education for non‐transfusion medicine physicians: a structured review

Abstract: As transfusion is a commonly identified overused intervention, there is a clear gap between evidence-based and clinical practice. To close this gap, there is not only a need for increased transfusion medicine educational opportunities but for those using structured and proven instructional methods. Kern and colleagues have defined important steps to be considered in curricular design: general needs assessment; targeted needs assessment; goals and objectives; educational strategies; implementation; and evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 60 publications
2
28
0
1
Order By: Relevance
“…Transfusion Camp will be described according to Thomas and Kern's approach to curriculum development in medical education . The target audience is non–hematology specialty–based postgraduate trainees, although postgraduate trainees from hematology and hematopathology are also encouraged to attend.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfusion Camp will be described according to Thomas and Kern's approach to curriculum development in medical education . The target audience is non–hematology specialty–based postgraduate trainees, although postgraduate trainees from hematology and hematopathology are also encouraged to attend.…”
Section: Methodsmentioning
confidence: 99%
“…One of the challenges in delivering TM education is determining the optimal time in training to deliver such content. Recent reviews advocate for TM education at the beginning of clinical training, either in medical school or early in the postgraduate training period, so as to tailor to the specialty . However, several studies have shown that TM knowledge at this level is deficient .…”
mentioning
confidence: 99%
“…(24) The active teaching methodology seems to be more effective, especially if adapted to the undergraduate course and the specialty of residency. (25) Teaching based on specific skills applied to clinical cases favors student learning. (26) A Brazilian study assessed knowledge of sixth-year undergraduate medical students and residents of several areas.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…In health education, games have been used to improve the performance of health professionals, by improving their knowledge and skills (15). Although further studies are required to prove their efficiency as an educational strategy, several experiences have demonstrated positive results regarding user acceptance, motivation, and increased interest in the addressed subjects (2).…”
Section: Discussionmentioning
confidence: 99%
“…Quiz-type games have already been successfully applied in the medical field for teaching genetics, physiology, and dermatology, among others (4,14,23). In transfusion medicine, e-mails with quizzes (Transfusion News, Question of the Day, https://transfusionnews.com/path-questions/) have been applied for the continuing education of professionals in this area in several countries (15). Abney et al 1pointed out strategies so that online quizzes can be used in an integrated manner with the traditional curriculum in medical education.…”
Section: Discussionmentioning
confidence: 99%